Influence of lobbying in EU policy process phases - Serna-Ortega, Álvaro; Almansa-Martínez, Ana; Castillo-Esparcia, Antonio (Frontiers in Political Science, 2025)
The influence of lobbies in the European Union is a complex phenomenon that must be analyzed through various direct and indirect conditioning dimensions. This theoretical research examines the impact of pressure groups at each of the six stages of the public policy formulation process in the supranational entity: problem emergence in society, agenda setting, consideration of policy options, decision-making, policy implementation, and policy evaluation. The study reveals how the influence of lobbies fluctuates depending on the point in the process and the type of interests they represent. Lobbies with social interests tend to have an advantage in phases involving public engagement, using grassroots lobbying strategies. On the other hand, economic lobbies dominate in phases that require contact with legislators, employing direct communication strategies. Among the direct conditioning dimensions, economic capacity–whether explicitly or implicitly−and access to decision-makers are crucial factors in determining the degree of influence. Additionally, in terms of indirect dimensions, media coverage is considered the most explanatory element regarding the influence capacity of lobbies, particularly at the initial and final stages of the governance cycle.